Transcultural images in Hollywood cinema debates on migration, identity, and finance - Baloğlu, Uğur; Birincioğlu, Yıldız Derya (Communication, globalization, and cultural identity., 2021)
"Transcultural Images in Hollywood Cinema examines the transnational and transcultural characteristics of Hollywood cinema. The narrative, cinematographic, and aesthetic structures of Hollywood cinema are turned upside down as chapters analyze gender, social, cultural, and economic-political contexts"--